Breakage is the norm: use of condoms and lubrication in anal sex among Black South African men who have sex with men. Issue 4 (3rd April 2017) - Lee, Matthew; Sandfort, Theo; Collier, Kate; Lane, Tim; Reddy, Vasu
Abstract: This paper explores condom use and lubrication practices among Black men who have sex with men in South African townships. Results are from 81 in-depth individual interviews conducted among a purposive sample from four townships surrounding Pretoria as part of a larger qualitative study. Awareness that condoms should be used to have safer anal sex was ubiquitous. Fewer men reported that lubricants should be used to facilitate anal intercourse. Partner pressure and partner distrust were the most common barriers cited for not using condoms and lubricants. Knowledge about condom-lubricant compatibility was rare. Condom problems were a norm, with widespread expectations of condom failure. Men's subjectivities – their perceptions of and preferences for specific brands, types and flavours of condoms and lubricants – influenced engagement with such safer-sex technologies. However, what was available in these settings was often neither what men needed nor preferred. Findings show the need to enhance access to appropriate and comprehensive: safer-sex supplies, health services and health education, and underline the importance of efforts to develop targeted programmes relevant to experiences of men who have sex with men in the South African context.